2020
DOI: 10.1111/apt.15618
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes in a large North American cohort living with chronic hepatitis B virus: a cross‐sectional analysis

Abstract: Summary Background Patient‐reported outcomes (PROs) such as health‐related quality of life (HRQoL) and symptoms associated with chronic hepatitis B viral (HBV) infection have not been well‐described in North American cohorts. Aims To evaluate several PROs and associations with HBV disease activity markers. Methods Cross‐sectional analysis including 876 adults who completed PRO measures during the Hepatitis B Research Network Adult Cohort Study. Participants on HBV treatment were excluded. Outcomes included: HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…Fears about personal health can also be exacerbated by the physical symptoms of the disease. In large, multi-national studies of patient-reported CHB outcomes [41,42], poorer health-related quality of life is consistently related to advanced liver disease. Anxiety and other depressive symptoms are common, particularly as physical symptoms manifest due to advancing liver disease [43][44][45][46].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fears about personal health can also be exacerbated by the physical symptoms of the disease. In large, multi-national studies of patient-reported CHB outcomes [41,42], poorer health-related quality of life is consistently related to advanced liver disease. Anxiety and other depressive symptoms are common, particularly as physical symptoms manifest due to advancing liver disease [43][44][45][46].…”
mentioning
confidence: 99%
“…Anxiety and other depressive symptoms are common, particularly as physical symptoms manifest due to advancing liver disease [43][44][45][46]. In contrast, those without symptoms of liver disease report lower (but still present [47]) impacts on mental well-being in relation to health-related matters [41,42].…”
mentioning
confidence: 99%
“…The SCL is a 10‐item instrument originally developed by the NIDDK to quantify symptoms associated with chronic liver disease. It has been modified for utilisation in several NIDDK‐funded research networks of various liver disease populations 7,9 . Participants were asked, “ During the last month, how much have you been bothered by the following symptom: fatigue, itching, pain over liver, irritability, depression/sadness, nausea, poor appetite, weight loss, dark urine, jaundice .” For each symptom, the participant marked a box to indicate how bothered they were by the symptom in the last month: None at all (0), A little bit (1), moderately (2), quite a bit (3), or extremely (4).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked, “ During the last month, how much have you been bothered by the following symptom: fatigue, itching, pain over liver, irritability, depression/sadness, nausea, poor appetite, weight loss, dark urine, jaundice .” For each symptom, the participant marked a box to indicate how bothered they were by the symptom in the last month: None at all (0), A little bit (1), moderately (2), quite a bit (3), or extremely (4). If they did not have the symptom, they marked “None at all.” For this analysis, a total CHB symptom score was created at each study visit by summing the 10 symptom scores with a possible range from 0 to 40, with higher scores indicating worse symptoms 7 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation